Environmental risk factors, protective factors, and biomarkers for postpartum depressive symptoms: an umbrella review. (September 2022) - Kim, Jae Han; Kim, Jong Yeob; Lee, Seul; Lee, San; Stubbs, Brendon; Koyanagi, Ai; Dragioti, Elena; Jacob, Louis; Carvalho, Andre F.; Radua, Joaquim; Thompson, Trevor; Smith, Lee; et al.
Abstract: We performed an umbrella review on environmental risk/protective factors and biomarkers for postpartum depressive symptoms to establish a hierarchy of evidence. We systematically searched PubMed, Embase, and the Cochrane Database of Systematic Reviews from inception until 12 January 2021. We included systematic reviews providing meta-analyses related to our research objectives. Methodological quality was assessed by AMSTAR 2, and the certainty of evidence was evaluated by GRADE. This review was registered in PROSPERO (CRD42021230784). We identified 30 articles, which included 45 environmental risk/protective factors (154, 594 cases, 7, 302, 273 population) and 9 biomarkers (2018 cases, 16, 757 population). The credibility of evidence was convincing (class I) for antenatal anxiety (OR 2.49, 1.91–3.25) and psychological violence (OR 1.93, 1.54–2.42); and highly suggestive (class II) for intimate partner violence experience (OR 2.86, 2.12–3.87), intimate partner violence during pregnancy (RR 2.81, 2.11–3.74), smoking during pregnancy (OR 2.39, 1.78–3.2), history of premenstrual syndrome (OR 2.2, 1.81–2.68), any type of violence experience (OR 2.04, 1.72–2.41), primiparity compared to multiparity (RR 1.76, 1.59–1.96), and unintended pregnancy (OR 1.53, 1.35–1.75). Highlights: We established the level of evidence for each environmental factor and biomarker of postpartum depressive symptoms. Majority of included studies used a questionnaire for diagnosis rather than the DSM or ICD. Only antenatal anxiety and psychological violence were convincingly associated with postpartum depressive symptoms. No environmental protective factors and biomarkers of postpartum depressive symptoms showed robust association.